Costs of employee smoking in the workplace in Scotland. Issue 2 (1st June 2000) - Parrott, Steve; Godfrey, Christine; Raw, Martin
Abstract : BACKGROUND: Employers have responded to new regulations on the effects of passive smoking by introducing a range of workplace policies. Few policies include provision of smoking cessation intervention. OBJECTIVE: To estimate the cost to employers of smoking in the workplace in Scotland to illustrate the potential gains from smoking cessation provision. Costs vary with type of smoking policy in place; therefore, to estimate these costs results from a survey were combined with evidence drawn from a literature review. STUDY DESIGN: A telephone survey of 200 Scottish workplaces, based on a stratified random sample of workplaces with 50 or more employees, was conducted in 1996. Additional evidence was compiled from a review of the literature of smoking related costs and specific smoking related effects. RESULTS: 167 completed responses were received, of which 156 employers (93%) operated a smoking policy, 57 (34%) operated smoke free buildings, and 89 (53%) restricted smoking to a "smoke room". The research literature shows absenteeism to be higher among smokers when compared to non-smokers. The estimated cost of smoking related absence in Scotland is £40 million per annum. Total productivity losses are estimated at approximately £450 million per annum. In addition, the resource cost in terms of losses from fires caused by smoking materials is estimated at approximately £4 million per annum. In addition, there are costs from smoking related deaths and smoking related damage to premises. CONCLUSION: This study shows how smoking cessation interventions in the workplace can yield positive cost savings for employers, resulting in gains in productivity and workplace attendance which may outweigh the cost of any smoking cessation programme.